Isotherm‑kinetic equilibrium investigations on absorption remediation potential for COD and ammoniacal nitrogen from leachate by the utilization of paper waste sludge as an eco‑friendly composite fller - Detho, Amir; Abdul Kadir, Aeslina; Rassem, Hesham Hussein Rassem (2024)
The paper industry is a major environmental polluter due to paper waste sludge (PWS), often disposed of in hazardous ways. The techniques are employed to disposing of PWS are posing signifcant environmental hazards and risks to wellbeing. This study aims to evaluate PWS as a potential replacement for commercial adsorbents like AC and ZEO in treating stabilized leachate. Contact angle analysis of PWS was 92.60°, reveals that PWS to be hydrophobic. Batch adsorption experiments were conducted with parameters set at 200 rpm stirring speed, 120 min contact time, and pH 7. Optimal conditions for COD and NH3–N removal were identifed at 120 min contact time, 200 rpm stirring speed, pH 7, and 2.0 g PWS ratio. Removal percentages for COD and NH3–N were 62% and 52%, respectively. Based on the results of the isotherm and kinetic studies, it was observed that the Langmuir and Pseudo second order (PSO) model exhibited greater suitability compared to the Freundlich and Pseudo frst order (PFO) model, as indicated by higher values of Rsquared (R2). The Rsquared of Langmuir for COD and NH3–N were 0.9949 and 0.9919 and for Freundlich model were 0.9855 and 0.9828 respectively. Whereas the Rsquared of PFO for COD and NH3–N were 0.9875 and 0.8883 and for PSO were 0.9987 and 0.9909 respectively.